SWOT-AHP analysis of youth participation in South Sulawesi, Indonesia, palm sugar agroforestry - ERNAWATI ERNAWATI; SYAHIDAH SYAHIDAH; A. MUJETAHID (Smujo International, 2026)
Abstract. Ernawati, Syahidah, Mujetahid A. 2026. SWOT-AHP analysis of youth participation in South Sulawesi, Indonesia, palm sugar agroforestry. Asian J Agric 10: g100103. https://doi.org/10.13057/asianjagric/g100103. Youth disengagement from agroforestry-based livelihoods threatens the continuity of palm sugar production and the broader non-timber forest product economy in South Sulawesi, Indonesia. This study examines factors influencing youth participation in palm sugar agroforestry and prioritizes actionable strategies to strengthen youth engagement in the Universitas Hasanuddin Educational Forest (KHDTK) landscape. Data were collected through household surveys, semi-structured expert interviews, and field observations in Rompegading and Limapoccoe Villages. An integrated SWOT-AHP approach was applied to (i) identify internal and external factors shaping youth participation, (ii) formulate strategic alternatives, and (iii) rank strategies based on expert judgments and derived priority weights. The results highlight that the most influential strategic priorities focus on value-added product innovation and the expansion of digital/social-media marketing, supported by capacity building and institutional strengthening to improve product quality, coordination, and market access. Taken together, the results suggest that palm sugar agroforestry becomes more appealing to young people when it is framed as a market-oriented agribusiness, with roles beyond traditional production such as product development, branding, and online customer engagement. The prioritized strategy package provides practical guidance for local stakeholders. It highlights targeted, youth-focused interventions that upgrade palm sugar enterprises and strengthen the attractiveness and viability of agroforestry-based livelihoods.